2003
DOI: 10.1128/aem.69.5.2498-2504.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Sequencing of a Poly( dl -Lactic Acid) Depolymerase Gene from Paenibacillus amylolyticus Strain TB-13 and Its Functional Expression in Escherichia coli

Abstract: The gene encoding a poly(DL-lactic acid) (PLA) depolymerase from Paenibacillus amylolyticus strain TB-13 was cloned and overexpressed in Escherichia coli. The purified recombinant PLA depolymerase, PlaA, exhibited degradation activities toward various biodegradable polyesters, such as poly(butylene succinate), poly(butylene succinate-co-adipate), poly(ethylene succinate), and poly(⑀-caprolactone), as well as PLA. The monomeric lactic acid was detected as the degradation product of PLA. The substrate specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…Recent studies including our work have demonstrated the presence of hydrolytic activity against polylactic acid (PLA), a biodegradable polyester, in several lipolytic enzymes and carboxylesterases315758. In this work, 26 purified metagenomic esterases were screened for PLA-degrading activity using an agarose plate assay with the emulsified PLA2 (M w 2 K).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies including our work have demonstrated the presence of hydrolytic activity against polylactic acid (PLA), a biodegradable polyester, in several lipolytic enzymes and carboxylesterases315758. In this work, 26 purified metagenomic esterases were screened for PLA-degrading activity using an agarose plate assay with the emulsified PLA2 (M w 2 K).…”
Section: Resultsmentioning
confidence: 99%
“…and Tritirachium album has been reported (Jarerat & Tokiwa, 2001;Nakamura et al, 2001). Nevertheless, an esterase as well as a lipase have also been linked to PLA degradation (Hoshino & Isono, 2002;Akutsu-Shigeno et al, 2003). More recently, a PBS-degrading enzyme from Aspergillus oryzae and a cutinase-like enzyme from Cryptococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…strain 41 (Pranamuda et al, 2001), Amycolatopsis sp. strain K104-1 , and Kibdelosporangium aridum ; serine protease from Tritirachium album (Williams, 1981) and Actinomadura keratinilytica strain T16-1 (Sukkhum et al, 2009b); alkaline protease from Bacillus lentus, Bacillus subtilis and Bacillus licheniformis (Oda et al, 2000); lipase (esterase) from Bacillus smithii strain PL21 (Sakai et al, 2001); lipase from Paenibacillus amylolyticus strain TB-13 (Akutsu-Shigeno et al, 2003); lipase (cutinase) from Cryptococcus sp. strain S-2 (Masaki et al, 2005); and esterase from Geobacillus thermocatenulatus (thermophilic) (Tomita et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…strain 41 (Pranamuda et al, 2001), and Amycolatopsis orientalis ssp. orientalis (Li et al, 2008), which belong to the family Pseudonocardiaceae; Actinomadura keratinilytica strain T16-1 in the family Thermomonosporaceae (Sukkhum et al, 2009b); thermophilic Bacillus smithii in the family Bacillaceae (Sakai et al, 2001); and Paenibacillus amylolyticus strain TB-13 in the family Paenibacillaceae (Akutsu-Shigeno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%